Digitālo tekstu sentimenta analīze - Gulbinskis, Igors (Latvijas Universitāte, 2010)
Zinātniskajā darbā tiek pētīta sentimenta analīze, tās pielietojumi, algoritmi un to efektivitāte. Darba gaitā tika izstrādāts sentimenta analīzes dzinis latviešu valodai, kas nosaka teksta semantisko orientāciju, izmantojot Turnija algoritmu. Uz izstrādātā dziņa bāzes tika uzprojektēta un izveidota sistēma, kas nosaka dienas noskaņojumu Latvijā, analizējot viedokļus, ko cilvēki izsaka dažādos interneta resursos.

This paper mainly focuses on sentiment analysis. The research work described in this document consists of two parts - theoretical and practical. Goal of theoretical part was to investigate and describe sentiment analysis, its use in real-world, algorithms and their efficiency. Practical goal was to design and implement sentiment analysis engine for Latvian language and a system called imho.lv. This system uses sentiment analysis engine to determine daily mood in Latvia by analyzing opinions that people have expressed in various web resources. All previously mentioned goals were successfully achieved and the results are presented in this document.
Sentiment analysis of digital texts
Keywords: Datorzinātne